2018
DOI: 10.1111/jvh.12937
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness of elbasvir/grazoprevir In HCV‐infected patients in the US veterans affairs healthcare system

Abstract: Elbasvir/grazoprevir (EBR/GZR) is an all-oral direct-acting antiviral agent (DAA) with high sustained virologic response (SVR) in clinical trials. This study's primary objective was to evaluate effectiveness of EBR/GZR among HCV-infected patients in a real-world clinical setting. We conducted a nationwide retrospective observational cohort study of HCV-infected patients in the US Department of Veterans Affairs (VA) using the VA Corporate Data Warehouse. The study population included patients with positive HCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 34 publications
10
30
0
Order By: Relevance
“…We are also unable to determine if an 8-week regimen was intended for participants in this study or if a longer 12-week treatment duration was intended but stopped early. Data from the present analysis are consistent with those reported previously by Kramer and colleagues [11]. This study included 2436 patients from the VA, of whom 1428 had HCV genotype 1b infection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We are also unable to determine if an 8-week regimen was intended for participants in this study or if a longer 12-week treatment duration was intended but stopped early. Data from the present analysis are consistent with those reported previously by Kramer and colleagues [11]. This study included 2436 patients from the VA, of whom 1428 had HCV genotype 1b infection.…”
Section: Discussionsupporting
confidence: 91%
“…In clinical trials, this combination therapy has demonstrated high rates of sustained virologic response (SVR) across a broad population of people with HCV infection, including those with chronic kidney disease, inherited blood disorders, compensated cirrhosis, and HCV/HIV co-infection [4][5][6][7][8][9][10]. The high SVR rates attained in elbasvir/grazoprevir clinical trials have also been replicated in the US Department of Veterans Affairs (VA) clinical practice populations, where an SVR rate of 95.6% was achieved in a large population comprised largely of male, black participants with HCV genotype 1 (genotype 1a, 34.7%; genotype 1b, 58.6%) infection, and more than 50% of whom had a history of drug or alcohol use [11]. The aim of this study was to assess elbasvir/grazoprevir regimens in individuals with chronic HCV genotype 1b infection from the VA population.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The study also uses accurate, laboratory test‐based definitions of HCV infection and SVR as well as DAA treatment based on pharmacy records. The observed overall SVR of 92.1% is consistent with effectiveness data for DAA in community‐based studies and further adds to the internal validity of the results …”
Section: Discussionsupporting
confidence: 83%
“…Despite the overall effectiveness of NS5A regimens, available treatments do not produce SVR in all patients. Up to 10% of genotype 1 patients who start ledipasvir/sofosbuvir do not achieve SVR and similar overall failure rates are reported for elbasvir/grazoprevir (2%‐8%) and ombitasvir/paritaprevir/ritonavir plus dasabuvir (1%‐11%) . In genotype 2 and 3 patients initiating sofosbuvir/velpatasvir, failure rates of 2% and 5%, respectively, were observed in clinical trials …”
Section: Introductionmentioning
confidence: 58%